Manajemen Bandwidth dan Manajemen Pengguna pada Jaringan Wireless Mesh Network dengan Mikrotik - Galeh Fatma Eko Ardiansa; Rakhmadhany Primananda; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
The development on the topology of the Internet network is now very wide, one of them is the topology of wireless mesh network (WMN) which has several advantages compared to other wireless based network. From these developments, the use of the Internet on each user in one network can become irregular without any bandwidth management and user management. Based on these problems, the need for research that can be applied user management and bandwidth management in WMN topology, so it can be used to monitor internet usage in accordance with bandwidth management and user management. This research uses 4 nodes that make up WMN topology, one of them as a gateway that is connected directly with mikrotik and local server as database storage media to perform user management. Mikrotik main role is for bandwidth management in accordance with commands provided by the server so that bandwidth usage can be controlled in accordance with the bandwidth owned by the user. From the research finished done, got some conclusion. The first conclusion is the integration of server to mikrotik maupn otherwise can be done well with the results of self-healing test with an average of 27.5 seconds and self-configure 26 seconds. In addition, QoS testing on the network is not solid with an average gain of 10 tests ie the first user (Host 1) uploaded 0.04 Mbps download of 0.512 Mbps, the second user (Host 2) uploaded 0.113 Mbps download of 0.971 Mbps , And a third user (Host 3) uploaded 0.238 Mbps download of 1,942 Mbps, the test also performed on solid network obtained average of first user uploaded 0.051 Mbps download of 0.488 Mbps, second user upload of 0.113 Mbps download of 0.976 Mbps, And the third user uploaded 0.251 Mbps download of 1.962 Mbps, from the test results can be the second conclusion that the bandwidth management is able to do well by the system, and the third conclusion is the user management can be done by the server from the results of design and testing on the system admin . From several test results and three points of conclusion, it can be concluded that the system is able to perform bandwidth management and user management well on the WMN network and WMN network is able to apply self-healing and self-configure well.